Analytical Approximations for the Maximum-to-mean Ratio of the E-field in a Reverberation Chamber: A Review - Xu, Qian; Jia, Rui; Geng, Lifei; Guo, Hao; Zhao, Yongjiu (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The expected value of the maximum value of the rectangular E-field is important in radiated susceptibility testing in a reverberation chamber. In this paper, different forms of equations for the maximum-to-mean ratio of the rectangular E-field are reviewed. Important derivations are summarized and detailed. It is interesting to note that some series which could be difficult to deal with from mathematics could be solved efficiently from physical point of view. The relationship between the independent sample number N and the parameters in generalized extreme value distribution is also given.